Reproductive biology of the leatherjacket, Meuschenia scaber (Monacanthidae) (Forster 1801) in the Hauraki Gulf, New Zealand. Issue 1 (2nd January 2018) - Visconti, Valerio; Trip, Elizabeth D. L.; Griffiths, Marc H.; Clements, Kendall D.
ABSTRACT: The leatherjacket Meuschenia scaber is widely distributed in Australasian waters, and is a valued bycatch of inshore bottom trawl fisheries although little is known of its life history. Here, we describe the reproductive biology of the species based on 651 leatherjackets sampled in the Hauraki Gulf, New Zealand, between July 2014 and March 2016. The maximum total length ( L T ) recorded for females and males were 320 and 315 mm, respectively, with both sexes present in all size classes. Monthly analysis of gonad condition revealed a clear spawning season from late austral winter to early summer (August–December), and histological analysis of the ovaries revealed that M. scaber is an indeterminate serial spawning gonochorist. The estimated sizes at sexual maturity ( L 50 ) for females (189.9 mm L T ) and males (188.4 mm L T ) did not differ significantly. Relatively small testes, sexual dimorphism and underwater observation of nesting suggest that M. scaber is a paired spawner.